PP.25.08: SERUM CALCIFICATION PROPENSITY IS ASSOCIATED WITH RENAL RESISTANCE INDEX AND TISSUE OXYGENATION IN PATIENTS WITH CKD OR HYPERTENSION. (June 2015) - Lu, Y.; Pasch, A.; Piskunowicz, M.; Hofmann, L.; Milani, B.; Stuber, M.; Vogt, B.; Pruijm, M.; Burnier, M.
Abstract : Objective: Arterial calcifications are associated with cardiovascular and all-cause mortality in patients with kidney disease and/or hypertension. A novel in vitro blood test has recently been developed to measure the calcification propensity of serum. It has been shown that a shorter maturation time of calciprotein particles (T50) is associated with greater vascular stiffness and lower all-cause survival in chronic kidney disease (CKD), but its associations with markers of renal vascular resistance and oxygenation have not been described. Design and method: In the LauBOLD (Lausanne Blood oxygenation level-dependent MRI) study, patients with CKD or arterial hypertension (AHT) underwent BOLD-MRI and renal Doppler ultrasound and were compared with healthy controls. The mean R2* values in the medulla and cortex were calculated, a high R2* value corresponds to a low oxygenation. Serum calcification propensity (T50) was determined in blood taken from the study participants. Aortic pulse wave velocity (PWV) was assessed as a measure of arterial stiffness by applanation tonometry using carotid and radial pulse waveforms. Results: 130 participants were included. Mean T50 was 242 ± 129 min in 52 CKD patients, 267 ± 117 min in 43 AHT patients, and 317 ± 105 min in 35 healthy controls (p anova = 0.015). In multivariable linear regression, adjusted for age, sex, body mass index, eGFR, mean arterial pressure, serum hemoglobin and glycemia levels, square-root transformed serum T50 correlated negatively with the outcome variables mean cortical (regression coefficient β±SE -0.20 ± 0.07, p = 0.003) and medullary (β -0.13 ± 0.05, p = 0.016) R2* level, ultrasound-assessed renal resistance index (β -0.005 ± 0.002, p = 0.009), and PWV (β -0.91 ± 0.04, p = 0.012). Conclusions: This study demonstrates that a high calcification propensity is associated with a lower renal tissue oxygenation and a higher intrarenal vascular resistance and vascular stiffness.